Development of Counting Bunny Board Mathematics Media to Improve Early Mathematics Skills of 5-6 Year Old Children - Jelita, Dea Putri; Sitorus, Ahmad Syukri (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
Media plays an important role in the learning process, and media is still often a problem for educators because of the lack of creativity in using it in the learning process to improve children's abilities, including early mathematics skills. Early mathematics skills in early childhood are important to be trained early on to prepare children for further education. In addition, children need to know and understand early mathematical concepts that can be used daily. Therefore, this study aims to develop Counting Bunny Board Mathematics media to improve children's early mathematics skills. This research was conducted with research subjects of group B Sentra Preparation students aged 5-6 years, with 17 children. The research method used by the researcher is Research and Development (R&D) with the ADDIE model consisting of 5 stages: analysis, design, development, implementation and evaluation. Data collection techniques in this Study used interview techniques, questionnaires, Material Expert and Media Expert Validation sheets and documentation. The data obtained were analyzed using descriptive, qualitative, and quantitative data analysis. The validation results show that the Counting Bunny Board Mathematics media is very feasible to be used as a learning media with a percentage of 100% and 97.5%, and the results of the product effectiveness trial showed an increase of 7.08% from the Pre-test-Post-test results. So this media can be used as an alternative for teachers to support learning